Caries-Free Prevalence among Schoolchildren in Malaysia-Time-Series Analysis of Trends and Projections from 1996 to 2030 - Lokman Najihah; Wan Zakiyatussariroh Wan Husin; Tengku Mardhiah Tengku Jalal; Jamaludin Marhazlinda (MDPI AG, 2023)
This study assessed caries-free prevalence trends over two decades from 1996 to 2019 and projected the caries-free prevalence from 2020 to 2030 among schoolchildren in Malaysia. The study consisted of secondary data analysis of caries-free prevalence from 1996 to 2019 in six-, twelve- and sixteen-year-old schoolchildren obtained from Health Information Management System (HIMS) reports. Three time-series models were compared: double exponential smoothing (DES), autoregressive integrated moving average (ARIMA) and the error, trend and seasonal (ETS) model, and the best model with the smallest error was chosen for univariate projection of caries-free prevalence of each age group until 2030. An upward trend of caries-free prevalence was observed for all age groups over the years. Caries-free prevalence was projected to increase with a different increment in each age group for the next decade, with a slightly damped trend noted in 16-year-old schoolchildren. Of all the age groups, the caries-free prevalence trend and projection demonstrated to be highest in 12-year-olds, followed by 16-year-olds, while 6-year-old schoolchildren revealed the lowest caries-free prevalence over three decades. The 16-year-old schoolchildren demonstrated the smallest predicted increment in caries-free prevalence. Future work can explore multivariate projections. Meanwhile, more resources and interventions could prioritise all age groups.